Bolivian Rhinotragini V: new species of Erythroplatys White, 1855, Rhinotragus Germar, 1824, Ornistomus Thomson, 1864, and Aechmutes Bates, 1867 (Coleoptera, Cerambycidae) - Clarke, Robin O.S. (Papéis Avulsos de Zoologia, 2012)
Bolivian Rhinotragini V: new species of Erythroplatys White, 1855, Rhinotragus Germar, 1824, Ornistomus Thomson, 1864, and Aechmutes Bates, 1867 (Coleoptera, Cerambycidae). Six new species are described: Erythroplatys boliviensis, Rhinotragus antonioi, Rhinotragus monnei, Ornistomus simulatrix, Aechmutes boliviensis, and Aechmutes subandinus. The female of Erythroplatys simulator Gounelle, 1911 is redescribed, and the male for the first time. Ornistomus bicinctus Thomson, 1864, Aechmutes lycoides Bates, 1867 and Aechmutes armatus Gounelle, 1911 are formally excluded from the fauna of Bolivia. All the species are illustrated, and host flower records provided.